Cross-border issues for digital platforms: A review of regulations applicable to Philippine digital platforms - Aiken Larisa O. Serzo (Philippine Institute for Development Studies (PIDS), 2020)
This Paper identifies certain policy issues in the existing regulatory infrastructure of the Philippines which may prevent digital platforms in the Philippines from innovating and participating in the global digital economy. In brief, these policy issues relate to the incoherence between the national innovation strategy of the government and the mishmash of regulations that digital platforms are subjected to. In particular, this relates to investment regulations, regulations on mass media, retail, advertising, logistics, telecommunications, and education. Such landscape has led to a regulatory environment that is unable to provide certainty as to the legality of the activities of Philippine-based digital platforms. There is a plethora of constitutional, statutory, and policy support for innovation, e-commerce, digitization, and entrepreneurship in the Philippines. However, there is a disconnect between these policies and the environment created by the actual implementation of the regulations. After the Introduction, Part II of this Paper will be a brief survey of the relevant laws and regulations relevant to digital platforms. This will focus on the areas of innovation policy, general electronic contracting, payments, consumer protection, data protection, cybercrime, access to funding, and intellectual property. Part III will then discuss the gaps in the laws and regulations vis a vis digital platforms, and Part IV will present how these gaps impact digital platforms. Finally, Part V proposes areas for policy consideration and regulatory review that aims to contribute to the shaping of a coherent and viable regulatory policy for Philippine digital platforms.
Keywords: 330; digital platforms; foreign direct investments; internet law; mass media; startups; internet economy; regulatory reform